Surveilling masses and unveiling human rights Uneasy choices for the Strasbourg Court - Kosta, Eleni (Tilburg University Press, 2017)
In this inaugural address I will first discuss the procedures in front of the UK IPT in the 10 Human Rights Organisations case, followed by a short presentation of the applications against actions of UK intelligence agencies in Big Brother Watch and in Bureau of Investigative Journalism that were directly submitted to the ECtHR. I will then turn to the issue of admissibility in secret surveillance cases, where the victims cannot prove that they have been directly affected by the surveillance measures, and will analyse the protection afforded by the ECtHR in light of its recent case law. After a short presentation of Articles 8 and 10 ECHR this inaugural address will focus on the discussion of the requirements that are established in Article 8(2) ECHR that when satisfied, justify an interference with the right to privacy: legality, legitimacy and necessity. The penultimate section will assess the recent case law of the CJEU in blanket data retention and surveillance cases. Finally I will close this inaugural address with a summary of my main findings and will conclude with thoughts for further research that I intend to undertake in the coming years.